Effects of Transendocardial Stem Cell Injection on Ventricular Proarrhythmia in Patients with Ischemic Cardiomyopathy: Results from the POSEIDON and TAC‐HFT Trials. (2nd March 2017) - Ramireddy, Archana; Brodt, Chad R.; Mendizabal, Adam M.; DiFede, Darcy L.; Healy, Chris; Goyal, Vishal; Alansari, Yahya; Coffey, James O.; Viles‐Gonzalez, Juan F.; Heldman, Alan W.; Goldberger, Jeffrey J.; Myerburg, Robert J.; et al.
Abstract: Transendocardial stem cell injection in patients with ischemic cardiomyopathy (ICM) improves left ventricular function and structure but has ill‐defined effects on ventricular arrhythmias. We hypothesized that mesenchymal stem cell (MSC) implantation is not proarrhythmic. Post hoc analyses were performed on ambulatory ECGs collected from the POSEIDON and TAC‐HFT trials. Eighty‐eight subjects (mean age 61 ± 10 years) with ICM (mean EF 32.2% ± 9.8%) received treatment with MSC ( n  = 48), Placebo ( n  = 21), or bone marrow mononuclear cells (BMC) ( n  = 19). Heart rate variability (HRV) and ventricular ectopy (VE) were evaluated over 12 months. VE did not change in any group following MSC implantation. However, in patients with ≥ 1 VE run (defined as ≥ 3 consecutive premature ventricular complexes in 24 hours) at baseline, there was a decrease in VE runs at 12 months in the MSC group ( p  = .01), but not in the placebo group ( p  = .07; intergroup comparison: p  = .18). In a subset of the MSC group, HRV measures of standard deviation of normal intervals was 75 ± 30 msec at baseline and increased to 87 ± 32 msec ( p =.02) at 12 months, and root mean square of intervals between successive complexes was 36 ± 30 msec and increased to 58.2 ± 50 msec ( p  = .01) at 12 months. In patients receiving MSCs, there was no evidence for ventricular proarrhythmia, manifested by sustained or nonsustained ventricular ectopy or worsened HRV. Signals of improvement in ventricular arrhythmias and HRV in the MSC group suggest a need for further studies of the antiarrhythmic potential of MSCs. Stem Cells Translational Medicine 2017;6:1366–1372